2013
DOI: 10.1590/s0102-09352013000600040
|View full text |Cite
|
Sign up to set email alerts
|

In vitro probiotic potential of Lactobacillus spp. isolated from fermented milks

Abstract: The potential of in vitro probiotic Lactobacillus spp. was evaluated in fermented milks marketed in Belo Horizonte, MG, Brazil. Of the samples analyzed, 86.7% had at least 10(6) CFU/mL of Lactobacillus spp., complying with the Brazilian quality standards for fermented milks. Furthermore, 56.7% had minimum count ranging from 10(8) to 10(9) CFU/mL, which is in accordance with legal parameters. The remaining 43.3% would not be able to satisfactorily guarantee benefits to consumers. The amount of Lactobacillus spp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…According to Cunha et al [ 18 ], the beneficial effect of a probiotic to its host is related to its concentration in the ileal lumen. The concentration required to obtain a clinical effect is at least 6–7 log cfu/mL or g in the ileum [ 18 , 115 ]. The ability of the starter cultures to attach onto the epithelium of the ileum at 7.3–8.0 log cfu/cm 2 ( Figure 2 ) is an excellent property.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Cunha et al [ 18 ], the beneficial effect of a probiotic to its host is related to its concentration in the ileal lumen. The concentration required to obtain a clinical effect is at least 6–7 log cfu/mL or g in the ileum [ 18 , 115 ]. The ability of the starter cultures to attach onto the epithelium of the ileum at 7.3–8.0 log cfu/cm 2 ( Figure 2 ) is an excellent property.…”
Section: Resultsmentioning
confidence: 99%
“…Traditional fermented foods exhibit a rich biodiversity of microorganisms from which probiotic microorganisms can be selected [12,13]. Indeed, many studies have reported a number of probiotic and potentially probiotic microorganisms from various fermented foods including kule naoto, bryndza cheese, hukati, hidal, dadhi, and dangke [14][15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%